(untitled) (KULT_online, 2010)
This monograph of Matthias Bickenbach and Harun Maye, both literary scholars and media theorists, aims at fulfilling two main objectives. On the one hand the study attempts to show how the notion of the Internet depends on the metaphor of surfing. To give reasons for their observation the authors argue that this media-metaphorical phenomenon is based on a long literary tradition of nautical metaphors which are meant to legitimate a bold handling of knowledge. On the other hand the authors advocate an appropriate handling of information in the Internet age. Thereby the claim for an educational policy of surfing entails a generalisation of the nautical imagery which is attended by the neglect of contemporary Internet metaphors.